“In the city of god” The advocacy of Mary by Miguel Suárez and the wall paintings at the Founder’s Manor in Tunja. New documents and interpretations. - Martínez Martín, Abel Fernando; Otálora Cascante, Andrés Ricardo; Espinoza Torres, María del Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This text exposes some documental sources gathered from the Regional Archive of Boyacá (RAB), which identify the relevance of Miguel Suárez de Figueroa, eldest son and heir to Gonzalo Suárez Rendón, founder of the city of Tunja, in charge of inishing and decorating of the roofs of the Founder’s Manor,as well as main sponsor and founder of Rosario Chapel, located in Santo Domingo church. Furthermore, an iconographic interpretation of the roof of the main hall in the Founder’s Manor is proposed, different from the one exposed by the historians Santiago Sebastián and José Miguel Morales Folguera.